2021
DOI: 10.4103/tjo.tjo_16_21
|View full text |Cite
|
Sign up to set email alerts
|

Update on the application of amniotic membrane in immune-related ocular surface diseases

Abstract: Immune-related ocular surface diseases, a group of diseases in which immune dysregulation damages the ocular surface, can induce uncontrolled inflammation and persistent epithelial defect, thus leading to the most severe forms of acute keratoconjunctivitis, dry eye disease, epithelial keratitis, stromal ulceration, and corneal perforation. As these diseases are often refractory to treatments, they have a threatening impact on the vision and life quality of patients. This review summarizes the current literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…However, in many SJS cases, the systemic condition is devastating, such as respiratory failure, which makes patients not suitable for invasive surgical intervention. ProKera ® offers the advantage of an easily performed technique, making it readily available for non-ophthalmic physicians, particularly in the bedside settings of intensive care units or emergency rooms [22]. We demonstrated one case of acute SJS (case 6) with complete remission and 2 cases of chronic SJS (cases 4 and 5) with chronic inflammation sequela.…”
Section: Discussionmentioning
confidence: 91%
“…However, in many SJS cases, the systemic condition is devastating, such as respiratory failure, which makes patients not suitable for invasive surgical intervention. ProKera ® offers the advantage of an easily performed technique, making it readily available for non-ophthalmic physicians, particularly in the bedside settings of intensive care units or emergency rooms [22]. We demonstrated one case of acute SJS (case 6) with complete remission and 2 cases of chronic SJS (cases 4 and 5) with chronic inflammation sequela.…”
Section: Discussionmentioning
confidence: 91%
“…Some immune-related reactions manifest on the ocular surface, such as uncontrolled inflammation, dry eye disease, epithelial keratitis, stromal ulceration and corneal perforation. [ 14 ] Thomas et al [ 15 ] reported a case of an 88-year-old Caucasian man with metastatic melanoma, who was administered pembrolizumab at 2 mg/kg. After 24 months of pembrolizumab therapy, he developed corneal erosions, oral and genital ulcerations, a syndrome similar to Behcet disease.…”
Section: Discussionmentioning
confidence: 99%
“…Articles related to conjunctivochalasis were included since the fornix may often be involved. Articles related to acute cicatrizing conjunctivitis, such as Stevens-Johnson syndrome were reviewed but not included in the summary as the literature has previously been comprehensively reviewed; 27,28 articles addressing the subacute and chronic pathology associated with cicatrizing conjunctivitis were included in the summary. A total of 62 articles were identified and included in the summary tables.…”
Section: Methodsmentioning
confidence: 99%
“…93 AMT placement for acute cicatrizing conjunctivitis has previously been reviewed and for this reason, a comprehensive summary of all articles was not included in this review paper. 27,28…”
Section: Eyelid and Fornixmentioning
confidence: 99%